2019
DOI: 10.1016/j.bbmt.2019.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus-Associated Post-Transplantation Lymphoproliferative Disease in Patients Who Received Anti-CD20 after Hematopoietic Stem Cell Transplantation

Abstract: transplantation lymphoproliferative disease (PTLD) is a serious complication associated with Epstein-Barr virus (EBV) infection after hematopoietic stem cell transplantation (HSCT). Although anti-CD-20 therapy is now used as a preemptive strategy for EBV reactivation, PTLD still occurs in some patients. Here we analyzed outcomes and risk factors associated with PTLD transformation in 208 HSCT recipients who were diagnosed with EBV-DNAemia and received at least 1 course of rituximab. The median patient age was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
(62 reference statements)
0
6
0
1
Order By: Relevance
“…Several studies have examined the association between EBV DNAemia or EBV-VL and the type of graft, considering as variable either HLA compatibility, [26][27][28][33][34][35][36]40,41,49,69 related/unrelated donor 6,14,25,26,33,42,69,85 or the combination of these characteristics 18,20,22,32,36,37,39,63,64 with very few significant associations found (only two studies reporting significant associations in adult/pediatric population 39,40 and one in pediatric patients 85 ). Some studies have considered the association between PTLD and HLA compatibility, 1,10,26,38,47,49,50 (one found a significant association 1 ) or between PTLD and related/unrelated donor 10,26,38,86 (none showing a significant association), or by combining HLA mismatched/matched and unrelated/related donor [46][47][48]…”
Section: F I G U R Ementioning
confidence: 99%
“…Several studies have examined the association between EBV DNAemia or EBV-VL and the type of graft, considering as variable either HLA compatibility, [26][27][28][33][34][35][36]40,41,49,69 related/unrelated donor 6,14,25,26,33,42,69,85 or the combination of these characteristics 18,20,22,32,36,37,39,63,64 with very few significant associations found (only two studies reporting significant associations in adult/pediatric population 39,40 and one in pediatric patients 85 ). Some studies have considered the association between PTLD and HLA compatibility, 1,10,26,38,47,49,50 (one found a significant association 1 ) or between PTLD and related/unrelated donor 10,26,38,86 (none showing a significant association), or by combining HLA mismatched/matched and unrelated/related donor [46][47][48]…”
Section: F I G U R Ementioning
confidence: 99%
“…PTLD represents a spectrum of lymphoproliferative disorders associated with EBV infection in the setting of pharmacologic immunosuppression 1 , 2 that usually occurs within 1 year of hematopoietic stem cell or solid organ transplantation. 2 Although PTLD is a common condition after hematopoietic stem cell transplantation with a reported incidence ranging from 1 to 17%, 2 , 3 ocular involvement remains a rare finding in this context. 4 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, no statistically significant association was found between the donor/recipient sex combination and post-transplant EBV infection [35,41,53,57,65]. Among all studies that examined the sex of the dyad donor/recipient and PTLD [57,82,94,98], only one [82] found a statistically significant association suggesting a higher risk of PTLD in patients who received a transplant from a different sex donor.…”
Section: Other Risk Factorsmentioning
confidence: 96%
“…Other factors associated with PTLD include: (1) CD8 + count (≥median vs. <median) 30 days after HSCT (HR = 0.34 (0.13-0.92)), (2) prior HSCT ((HR = 2.6 (1.1-6.4)) [57], (RR = 3.5 [1.7-6.3)) [70]), (3) splenectomy (SHR = 4.81 (1.51-15.4)) [94], (4) infusion of mesenchymal stromal cells (SHR = 3.05 (1.25-7.48)) [94], (5) a stepwise increase of EBV-DNA by 1 log (HR = 2.9 (1.7-4.8)) [96], (6) HLA DRB1*11:01 (SHR = 4.85 (1.57-14.97)) [82], and (7) HLA mismatch (SHR = 5.89 (2.43-14.3)) [94]. Fujimoto et al [55] found that, compared to matched related donor grafts, the risk of PTLD is higher when using mismatched related donor grafts (HR…”
Section: Other Risk Factorsmentioning
confidence: 99%